Podoplanin expression is a prognostic biomarker but may be dispensable for the malignancy of glioblastoma. Issue 3 (10th November 2018) - Eisemann, Tanja; Costa, Barbara; Harter, Patrick N; Wick, Wolfgang; Mittelbronn, Michel; Angel, Peter; Peterziel, Heike
Abstract: Background: Treatment options of glioblastoma, the most aggressive primary brain tumor with frequent relapses and high mortality, are still very limited, urgently calling for novel therapeutic targets. Expression of the glycoprotein podoplanin correlates with poor prognosis in various cancer entities, including glioblastoma. Furthermore, podoplanin has been associated with tumor cell migration and proliferation in vitro; however, experimental data on its function in gliomagenesis in vivo are still missing. Hence, we have functionally investigated the impact of podoplanin on glioblastoma in a preclinical mouse model to evaluate its potential as a therapeutic target. Methods: Fluorescence activated cell sorting, genome-wide expression analysis, and clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated nuclease 9 (Cas9)–mediated deletion of podoplanin in patient-derived human glioblastoma cells were combined with organotypic brain slice cultures and intracranial injections into mice. Results: We defined a malignant gene signature in tumor cells with high podoplanin expression. The increase and/or maintenance of high podoplanin expression in serial transplantations and in podoplanin low -sorted glioblastoma cells during outgrowth indicated the association of high podoplanin expression and poor outcome. Unexpectedly, similar rates of proliferation, apoptosis, angiogenesis, and invasion were observed in control and podoplanin-deleted tumors. Accordingly, neither tumor growth nor survival was affected upon podoplanin loss. Conclusion: We report that tumor progression occurs independently of podoplanin. Thus, in contrast to previous suggestions, blocking of podoplanin does not represent a promising therapeutic approach. However, as podoplanin is associated with tumor aggressiveness and progression, we propose the cell surface protein as a biomarker for poor prognosis.